Upaya Wali Kelas VII C Dalam Mengatasi Perilaku Prokrastinasi Akademik Di MTsN 8 Banyuwangi - Maola, Yara Husna; Hidayati, Diah Nur; H, Ibtida’ul Faizah Al; Fitriana, Ani Qotuz Zuhro’ (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
The purpose of this study was to find out the efforts of the homeroom teacher in overcoming academic procrastination at MTsN 8 Banyuwangi, namely by knowing the causes of students doing academic procrastination and the efforts of the homeroom teacher in overcoming academic procrastination. The method used in this research is in the form of descriptive qualitative research. The results of this study state that the efforts given by the homeroom teacher in overcoming academic procrastination in students are by providing motivation to build character in students. Providing internal and external motivation to students, so that students have high motivation in carrying out academic assignments by not delaying assignments from the teacher.